Possible rodent equivalent of the posterior cingulate cortex (area 23) interconnects with multimodal cortical and subcortical regions - Xiang, Xiao-Jun; Chen, Sheng-Qiang; Zhang, Xue-Qin; Chen, Chang-Hui; Zhang, Shun-Yu; Cai, Hui-Ru; Ding, Song-Lin (Frontiers in Neuroscience, 2023)
Posterior cingulate cortex (area 23, A23) in human and monkeys is a critical component of the default mode network and is involved in many diseases such as Alzheimer’s disease, autism, depression, attention deficit hyperactivity disorder and schizophrenia. However, A23 has not yet identified in rodents, and this makes modeling related circuits and diseases in rodents very difficult. Using a comparative approach, molecular markers and unique connectional patterns this study has uncovered the location and extent of possible rodent equivalent (A23~) of the primate A23. A23 ~ but not adjoining areas in the rodents displays strong reciprocal connections with anteromedial thalamic nucleus. Rodent A23 ~ reciprocally connects with the medial pulvinar and claustrum as well as with anterior cingulate, granular retrosplenial, medial orbitofrontal, postrhinal, and visual and auditory association cortices. Rodent A23 ~ projects to dorsal striatum, ventral lateral geniculate nucleus, zona incerta, pretectal nucleus, superior colliculus, periaqueductal gray, and brainstem. All these findings support the versatility of A23 in the integration and modulation of multimodal sensory information underlying spatial processing, episodic memory, self-reflection, attention, value assessment and many adaptive behaviors. Additionally, this study also suggests that the rodents could be used to model monkey and human A23 in future structural, functional, pathological, and neuromodulation studies.